Catalysts: Stabilization of Single Metal Atoms on Graphitic Carbon Nitride (Adv. Funct. Mater. 8/2017). (February 2017) - Chen, Zupeng; Mitchell, Sharon; Vorobyeva, Evgeniya; Leary, Rowan K.; Hauert, Roland; Furnival, Tom; Ramasse, Quentin M.; Thomas, John M.; Midgley, Paul A.; Dontsova, Dariya; Antonietti, Markus; Pogodin, Sergey; et al.
Abstract : In article number 1605785, Javier Pérez‐Ramírez and co‐workers investigate the synthesis of single‐atom heterogeneous catalysts based on precious metals and using graphitic carbon nitride as the carrier. Advanced characterization and simulations reveal the impact of the carrier properties, and of the metal identity and method of introduction on the speciation. Controlling the metal‐carrier interaction and exposing the reactive metal centers are key for maximizing the potential of these materials.